Pengaruh Socioemotional Wealth Terhadap Keputusan Struktur Modal Usaha Mikro, Kecil, dan Menengah - Lusianus Heronimus Sinyo Kelen (Jurnal Ilmu Manajemen dan Bisnis, 2022)
If a business wants to "upgrade", it needs a strategy to use debt, so that it can make the business continue in the future. This study aims to prove the pecking order theory in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Specifically, this study wanted to examine the effect of socioemotional wealth on the capital structure decisions of MSME owners supporting tourism in Kabupaten Sumba Timur, Propinsi Nusa Tenggara Timur. The selection of MSMEs supporting tourism is because tourism growth in East Sumba Regency is increasing and requires businesses to support tourism. The research sample was 101 respondents spread over two sub-districts (Kambera and Kota Waingapu) which are the centers of MSMEs in Kabupaten Sumba Timur. This study uses a probit regression analysis technique because the dependent variable uses a dummy variable that is included in the nominal scale with the independent variable using an interval scale. The results show that socioemotional wealth affects capital structure decisions, where the higher the socioemotional wealth of MSME owners, the less likely they are to use debt in their business.